Critical perspectives on ageing societies - Bernard, Miriam; Scharf, Thomas (Ageing and the lifecourse., 2007)
This important new book brings together some of the best known international scholars working within a critical gerontology perspective to review and update our understanding of how the field has developed over the last twenty-five years and provide a challenging assessment of the complex practical and ethical issues facing older people, and those who conduct research on ageing, in the 21st century.